Silva mind control method eaudiobook The revolutionary program by the founder of the world's most famous mind control course. - José, Silva (Simon & Schuster Audio, 2022)
The revolutionary program that teaches you how to use meditation and visualization to change your life. First published in 1978, The Silva Mind Control Method has helped millions of people create better, happier, and more successful lives. Based on the extraordinary course pioneered by José Silva in the 1960s, this accessible guidebook uses meditation and visualization to help you alleviate stress, overcome bad habits and emotional insecurity, increase creativity, develop concentration, harness your dreams, and deepen your relationships. Featuring transformative advice and fascinating case studies, this revolutionary book teaches you to use your mind at a deeper and more effective level and reveal its extraordinary power.